Role of phenolic compounds in peptic ulcer: An overview - Sabiha Sumbul; Mohd. Aftab Ahmad; Mohd. Asif; Mohd. Akhtar (Wolters Kluwer Medknow Publications, 2011)
Peptic ulcer is the most common gastrointestinal tract (GIT) disorder in clinical practice, which affects approximately 5-10% of the people during their life. The use of herbal drugs for the prevention and treatment of various diseases is constantly developing throughout the world. This is particularly true with regard to phenolic compounds that probably constitute the largest group of plants secondary metabolites. Phenolic compounds have attracted special attention due to their health-promoting characteristics. In the past ten years a large number of the studies have been carried out on the effects of phenolic compounds on human health. Many studies have been carried out that strongly support the contribution of polyphenols to the prevention of cardiovascular diseases, cancer, osteoporosis, neurodegenerative diseases, and diabetes mellitus, and suggest a role in the prevention of peptic ulcer. Polyphenols display a number of pharmacological properties in the GIT area, acting as antisecretory, cytoprotective, and antioxidant agents. The antioxidant properties of phenolic compounds have been widely studied, but it has become clear that their mechanisms of action go beyond the modulation of oxidative stress. Various polyphenolic compounds have been reported for their anti-ulcerogenic activity with a good level of gastric protection. Besides their action as gastroprotective, these phenolic compounds can be an alternative for the treatment of gastric ulcers. Therefore, considering the important role of polyphenolic compounds in the prevention or reduction of gastric lesions induced by different ulcerogenic agents, in this review, we have summarized the literature on some potent antiulcer plants, such as, Oroxylum indicum, Zingiber officinale, Olea europaea L., Foeniculum vulgare, Alchornea glandulosa, Tephrosia purpurea, and so on, containing phenolic compounds, namely, baicalein, cinnamic acid, oleuropein, rutin, quercetin, and tephrosin, respectively, as active constituents.